Catastrogenesis: DM, GWs, and PBHs from ALP string-wall networks. Issue 2 (1st February 2023) - Gelmini, Graciela B.; Simpson, Anna; Vitagliano, Edoardo
Abstract: Axion-like particles (ALPs), a compelling candidate for dark matter (DM), are the pseudo Nambu-Goldstone bosons of a spontaneously and explicitly broken global U(1) symmetry. When the symmetry breaking happens after inflation, the ALP cosmology predicts the formation of a string-wall network which must annihilate early enough, producing gravitational waves (GWs) and primordial black holes (PBHs), as well as non-relativistic ALPs. We call this process catastrogenesis . We show that, under the generic assumption that the potential has several degenerate minima, GWs from string-wall annihilation at temperatures below 100 eV could be detected by future CMB and astrometry probes, for ALPs with mass from 10 -16 to 10 6 eV. In this case, structure formation could limit ALPs to constitute a fraction of the DM and the annihilation would produce mostly "stupendously large" PBHs. For larger annihilation temperatures, ALPs can constitute 100% of DM, and the annihilation could produce supermassive black holes with a mass of up to 10 9 M ⊙ as found at the center of large galaxies. Therefore our model can solve two mysteries, the nature of the DM and the origin of these black holes.